Recent Trends in Virtual Reality for Meaningful and Fun Science Learning: A Systematic Literature Review - Iwan Purnama; Arie Wahyu Prananta; Tiok Wijanarko (Jurnal Penelitian Pendidikan IPA, 2024)
The use of Virtual Reality in education can revolutionize the learning experience of students through immersive and captivating encounters that can enhance their understanding of the subject can provide a meaningful and enjoyable Virtual Reality experience. Where the research objective is to examine the latest trends in Virtual Reality for meaningful and enjoyable science learning: Systematic Literature Review. The review was conducted based on state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines. The results of this research explain that there are Learning Trends in the Future, namely: Collaboration, Learning Inspiration from a Young Age, Rapidly Growing Online Learning, Using Virtual Reality for Learning, Learning with AI Technology; Uses of Virtual Reality in science learning: Use of Virtual Reality as a learning medium, Use of Virtual Reality as a competency testing medium, Learning & competency testing in the Film Industry; The essence of science learning: Science as a way of thinking, Science as a way of inquiry, Science as a building of knowledge, Science as a form of interaction between technology and society.